CYP2C19 Genotype‐Guided Antiplatelet Therapy After Percutaneous Coronary Intervention in Diverse Clinical Settings - Amber L. Beitelshees; Cameron D. Thomas; Philip E. Empey; George A. Stouffer; Dominick J. Angiolillo; Francesco Franchi; Sony Tuteja; Nita A. Limdi; James C. Lee; Julio D. Duarte; Rolf P. Kreutz; Todd C. Skaar; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Studies have demonstrated increased risk of major atherothrombotic events in CYP2C19 loss‐of‐function (LOF) variant carriers versus non‐carriers treated with clopidogrel after percutaneous coronary intervention (PCI). We sought to evaluate real‐world outcomes with the clinical implementation of CYP2C19‐guided antiplatelet therapy after PCI. Methods and Results Data from 9 medical centers where genotyping was performed in the setting of PCI were included. Alternative therapy with prasugrel or ticagrelor was recommended for patients with a CYP2C19 LOF variant. The primary outcome was the composite of major atherothrombotic events (all‐cause death, myocardial infarction, ischemic stroke, stent thrombosis, or hospitalization for unstable angina) within 12 months following PCI. Moderate or severe/life‐threatening bleeding within 12 months was a secondary outcome. Among 3342 patients, 1032 (31%) were LOF carriers, of whom 571/1032 (55%) were treated with alternative therapy. In LOF carriers, the rate of major atherothrombotic events was lower in patients treated with alternative therapy versus clopidogrel (adjusted HR, 0.56; 95% CI 0.39–0.82). In those without a LOF allele, no difference was observed (adjusted HR, 1.07; 95% CI 0.71–1.60). There was no difference in bleeding with alternative therapy versus clopidogrel in either LOF carriers or those without a LOF allele. Conclusions Real‐world data demonstrate lower atherothrombotic risk in CYP2C19 LOF carriers treated with alternative therapy versus clopidogrel and similar risk in those without a LOF allele treated with clopidogrel or alternative therapy. These data suggest that PCI patients treated with clopidogrel should undergo genotyping so that CYP2C19 LOF carriers can be identified and treated with alternative therapy.